Obesity and Periodontal Diseases: The Emerging Role of Metabolic Health and Chronic Inflammation in Oral Disease - Kala-Kaziszyn, Ewa; Smagowska, Julia; Biskup, Alicja; Wnęk, Agata (Quality in Sport, 2026)
Obesity is a chronic metabolic disease characterized by excessive adipose tissue accumulation and persistent low-grade systemic inflammation. Periodontitis is one of the most common chronic inflammatory diseases worldwide and represents a major cause of tooth loss in adults. Increasing evidence suggests that obesity may contribute to the development and progression of periodontal diseases through shared inflammatory and metabolic pathways. The aim of this review was to summarize current evidence regarding the relationship between obesity and periodontal diseases, with particular emphasis on biological mechanisms, epidemiological findings, and clinical implications. A narrative review of the literature was conducted using PubMed/MEDLINE, Scopus, and Web of Science databases. Available evidence consistently demonstrates a positive association between obesity and periodontitis. Meta-analyses report increased odds of periodontal disease among individuals with obesity, with estimated odds ratios ranging from 1.31 to 2.46. Proposed mechanisms include chronic low-grade inflammation, dysregulated adipokine secretion, enhanced osteoclastogenesis, insulin resistance, oxidative stress, and obesity-associated alterations in the oral and gut microbiome. Current evidence supports obesity as an important potential risk factor for periodontal diseases. The interaction between metabolic dysfunction and periodontal inflammation highlights the need for a multidisciplinary approach integrating oral health assessment with metabolic risk evaluation. Further prospective and interventional studies are required to clarify causality and determine whether weight reduction strategies can improve periodontal outcomes.